(untitled) (Research, Society and Development, 2022)
The objective was to analyze the benefits that breaks can provide to telemarketers as a means of preventing neck pain and low back pain. As for the methodological approach, the research followed the principles suitable for narrative review without defining a systematic and replicable methodology at the level of data reproduction and quantitative results for specific questions. It was attested that the misuse of work equipment, associated with inadequate working postures and disorganization of tasks presented the existence of ergonomic risk to the worker, being possible the occurrence of damages to physical health, as well as small rest intervals can be decisive in the workers’ quality of life. It is considered as future research proposals, studies that carry out analysis with the application of breaks in the work environment of telephone attendants, so that it is applied in an ergonomic way in the environment and within the reality of a certain scope.